Transparent conductive film

JP7936709B2Active Publication Date: 2026-10-16NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022174260
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2026-10-16
Estimated Expiration
2042-10-31

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、金属ナノワイヤを含みながらも、着色の少ない透明導電性フィルムを提供することができる。また、本発明の透明導電性フィルムは、導電性に優れる点で有利である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936709000002
    Figure 0007936709000002
  • Figure 0007936709000001
    Figure 0007936709000001
Patent Text Reader

Abstract

To provide a transparent conductive film that includes metal nanowires while having less coloration.SOLUTION: A transparent conductive film comprises: a substrate; and a transparent conductive layer disposed on at least one side of the substrate, wherein the transparent conductive layer contains metal nanowires, the total light transmittance of the transparent conductive film is 60% or more, a surface resistance of the transparent conductive film is 10 Ω / sq. to 200 Ω / sq., and a ratio of absorbance at a wavelength of 360 nm to the absorbance at a wavelength of 550 nm (Abs(360nm) / Abs(550nm)) is 0.5 to 2.0 in the transparent conductive film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transparent conductive film.

Background Art

[0002] Conventionally, in image display devices having a touch sensor, a transparent conductive film obtained by forming a metal oxide layer such as ITO (indium-tin composite oxide) on a transparent resin film has been widely used as an electrode of the touch sensor. However, the transparent conductive film provided with this metal oxide layer has a problem that conductivity is easily lost due to bending, and it is difficult to be used in applications requiring flexibility such as flexible displays.

[0003] On the other hand, as a transparent conductive film with high flexibility, a transparent conductive film containing metal nanowires is known. A metal nanowire is a wire-shaped conductive substance having a nanometer-scale diameter. In a transparent conductive film composed of metal nanowires, the metal nanowires form a mesh shape, whereby a good electrical conduction path is formed with a small amount of metal nanowires, and openings are formed in the gaps of the mesh to achieve high light transmittance. However, in a transparent conductive film containing metal nanowires, coloring due to plasmon absorption poses a problem. As a method for solving this problem, Patent Document 3 controls the hue by adding nanoparticles, but since particles other than metal nanowires are added, there are problems such as increased resistance and increased haze.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of the Invention

[0005] This invention was made to solve the above-mentioned problems, and its objective is to provide a transparent conductive film that contains metal nanowires but exhibits minimal discoloration. [Means for solving the problem]

[0006] [1] The transparent conductive film of the present invention comprises a substrate and a transparent conductive layer disposed on at least one side of the substrate, wherein the transparent conductive layer contains metal nanowires, the total light transmittance of the transparent conductive film is 60% or more, the surface resistance of the transparent conductive film is 10Ω / □ to 200Ω / □, and the ratio of the absorbance of the transparent conductive film at a wavelength of 360nm to the absorbance at a wavelength of 550nm (Abs(360nm) / Abs(550nm)) is 0.5 to 2.0. [2] In the transparent conductive film described in [1] above, the standard deviation of the thickness of the metal nanowires may be 3 nm or more. [3] In the transparent conductive film of [1] or [2] above, the coefficient of variation of the thickness of the metal nanowire may be 0.13 to 0.4. [4] In any of the transparent conductive films described in [1] to [3] above, the metal nanowire may be a reduced product of a fibrous organometallic salt obtained by irradiating a solvent containing a metal compound and an organic acid with ultrasound in the air. [Effects of the Invention]

[0007] According to the present invention, it is possible to provide a transparent conductive film that contains metal nanowires but exhibits minimal coloration. Furthermore, the transparent conductive film of the present invention is advantageous in that it has excellent conductivity. [Brief explanation of the drawing]

[0008] [Figure 1] This is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. [Modes for carrying out the invention]

[0009] A. Transparent conductive film Figure 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. The transparent conductive film 100 comprises a substrate 10 and a transparent conductive layer 20 disposed on at least one side of the substrate 10. The transparent conductive layer contains metal nanowires.

[0010] The total light transmittance of the transparent conductive film described above is 60% or more. Preferably, the total light transmittance of the transparent conductive film is 80% or more, more preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. A higher total light transmittance of the transparent conductive film is preferable, but its upper limit is, for example, 98% (preferably 99%).

[0011] The surface resistance of the transparent conductive film described above is 10Ω / □ to 200Ω / □. According to the present invention, since metal nanowires can be incorporated with minimal influence on color, a transparent conductive film with excellent conductivity can be obtained. The surface resistance of the transparent conductive film is preferably 20Ω / □ to 150Ω / □, and more preferably 20Ω / □ to 100Ω / □. The surface resistance can be measured using Mitsubishi Chemical Analytec's "Automatic Resistivity Measurement System MCP-S620 type / MCP-S521 type".

[0012] The above-mentioned transparent conductive film has a ratio of absorbance at 360 nm to absorbance at 550 nm (Abs(360 nm) / Abs(550 nm)) of 0.5 to 2.0. Within this range, a transparent conductive film with minimal yellow tinting can be obtained. Using such a transparent conductive film, touch sensors and touch panels with excellent visibility can be obtained.

[0013] According to the present invention, by forming a transparent conductive layer with metal nanowires and specifying the surface resistance, total light transmittance, and (Abs(360nm) / Abs(550nm)) as described above, a transparent conductive film with excellent conductivity and light transmittance and high flexibility can be obtained. Furthermore, a transparent conductive film can be obtained that has less coloration originating from the metal nanowires (coloration caused by plasmon absorption) and can contribute to improved visibility. Such a transparent conductive film can be obtained, for example, by adjusting the light absorption spectrum to be broad. In one embodiment, the distribution of light absorption (and consequently, the coloration of the transparent conductive film) is controlled by the uniformity of the thickness of the metal nanowires. The discovery that the coloration of the transparent conductive film can be controlled by the uniformity of the thickness of the metal nanowires is one of the major achievements of the present invention.

[0014] The haze value of the transparent conductive film described above is preferably 20% or less, more preferably 10% or less, and even more preferably 0.1% to 5%.

[0015] B. Base material Any suitable material can be used to constitute the above-mentioned substrate. For example, the above-mentioned resin can be made from any suitable resin. This is because it has excellent smoothness of the substrate and wettability for the composition for forming the transparent conductive layer, and productivity can be greatly improved by continuous production using rolls.

[0016] In one embodiment, the substrate is made of a thermoplastic resin. Examples of thermoplastic resins include polyester resins, cycloolefin resins such as polynorbornene, acrylic resins, polycarbonate resins, and cellulose resins. Among these, polyester resins, cycloolefin resins, or acrylic resins are preferred. These resins are excellent in terms of transparency, mechanical strength, thermal stability, and moisture shielding properties. The thermoplastic resins may be used alone or in combination of two or more types. It is also possible to use optical films, such as low phase difference substrates, high phase difference substrates, phase difference plates, and brightness-enhancing films, as substrates.

[0017] The thickness of the above base material is preferably 20 μm to 200 μm, and more preferably 30 μm to 150 μm.

[0018] The total light transmittance of the above base material is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more.

[0019] The glass transition temperature of the resin constituting the above base material is preferably 80°C to 190°C, more preferably 100°C to 170°C, further preferably higher than 135°C and 170°C or lower, and particularly preferably higher than 140°C and 170°C or lower.

[0020] C.Transparent conductive layer As described above, the transparent conductive layer contains metal nanowires. The metal nanowire refers to a conductive substance that is made of metal, has a needle-like or thread-like shape, and has a nanometer-sized diameter. The metal nanowires may be linear or curved. If a transparent conductive layer composed of metal nanowires is used, the metal nanowires form a mesh structure, whereby a favorable electric conduction path can be formed even with a small amount of metal nanowires, and a transparent conductive film with low electric resistance can be obtained. Furthermore, since the metal nanowires form a mesh structure, openings are formed in the gaps of the mesh, and a transparent conductive film with high light transmittance can be obtained.

[0021] The ratio of the thickness d to the length L of the above-mentioned metal nanowire (aspect ratio: L / d) is preferably 5 to 100,000, more preferably 10 to 100,000, particularly preferably 20 to 10,000, and most preferably 20 to 1,000. By using metal nanowires with such a large aspect ratio, the metal nanowires intersect well, and high conductivity can be achieved with a small amount of metal nanowire. As a result, a transparent conductive film with high light transmittance can be obtained. In this specification, the length of the metal nanowire is the length of the longest part in the longitudinal direction of the metal nanowire as observed by an electron microscope (e.g., magnification: 5000x). The thickness of the metal nanowire is the length of the shortest part in the direction perpendicular to the longest part in the longitudinal direction of the metal nanowire as observed by an electron microscope (e.g., magnification: 50000x).

[0022] The thickness of the above-mentioned metal nanowire is preferably less than 500 nm, more preferably less than 400 nm, particularly preferably between 30 nm and 350 nm, and most preferably between 40 nm and 300 nm. Within this range, a transparent conductive layer with high light transmittance can be formed.

[0023] The number-average thickness of the metal nanowires is preferably 40 nm to 150 nm, and more preferably 50 nm to 100 nm. The number-average thickness of the metal nanowires, as well as the standard deviation and coefficient of variation described later, are determined by observing the transparent conductive layer with an electron microscope (for example, magnification: 50,000x), measuring the thickness of five randomly selected metal nanowires in each of five randomly selected areas (3.0 μm × 2.0 μm), and obtaining a total of 25 measurement points (5 areas × 5 wires).

[0024] The standard deviation of the thickness of the above metal nanowire is preferably 3 nm or more, more preferably 5 nm or more, and even more preferably 7 nm or more.

[0025] In this invention, by creating a non-uniform distribution of the thickness of the metal nanowires within a predetermined range (for example, by setting the standard deviation of the thickness of the metal nanowires within the above range), the absorption spectrum can be broadened. As a result, yellow coloration (coloration caused by plasmon absorption) can be suppressed, and a transparent conductive film with less color can be obtained.

[0026] The standard deviation of the thickness of the above-mentioned metal nanowires is preferably 25 nm or less, more preferably 20 nm or less, and even more preferably 15 nm or less. Within this range, a transparent conductive film with excellent light transmittance can be obtained.

[0027] The coefficient of variation of the thickness of the above-mentioned metal nanowire is preferably 0.13 to 0.4, more preferably 0.14 to 0.3, and even more preferably 0.15 to 0.25. Within this range, a transparent conductive film with minimal discoloration and excellent light transmittance can be obtained.

[0028] The length of the above-mentioned metal nanowire is preferably 1 μm to 1000 μm, more preferably 10 μm to 500 μm, and particularly preferably 10 μm to 100 μm. Within this range, a transparent conductive film with high conductivity can be obtained.

[0029] Any suitable metal can be used as the metal constituting the above-mentioned metal nanowire, as long as it is a conductive metal. Examples of metals constituting the above-mentioned metal nanowire include silver, gold, copper, and nickel. Materials that have been plated (for example, gold plated) of these metals may also be used. Among these, silver, copper, or gold are preferred from the viewpoint of conductivity, and silver is more preferred.

[0030] Any suitable method can be used to manufacture the above-mentioned metal nanowires. In one embodiment, examples include reducing silver nitrate in a solvent, applying a voltage or current from the tip of a probe to the surface of a precursor, drawing out metal nanowires at the tip of the probe, and continuously forming the metal nanowires. In the method of reducing silver nitrate in a solvent, silver nanowires can be synthesized by liquid-phase reduction of a silver salt such as silver nitrate in the presence of a polyol such as ethylene glycol and polyvinylpyrrolidone. Silver nanowires of uniform size can be mass-produced according to methods described, for example, in Xia, Y. et al., Chem. Mater. (2002), 14, 4736-4745, and Xia, Y. et al., Nano letters (2003) 3(7), 955-960. For example, the non-uniformity of the thickness of the metal nanowires can be adjusted by mixing and using metal nanowires manufactured under different manufacturing conditions. Furthermore, as a means of controlling the non-uniformity of the thickness of metal nanowires, for example, one method is to adjust the stability of the complex by changing the composition of the organic acid (the mixing ratio of acetic acid and propionic acid) in the ultrasonic manufacturing method described below.

[0031] In another embodiment, metal nanowires are obtained by reducing fibrous organometallic salts obtained by irradiating a solvent containing a metal compound and an organic acid with ultrasound in air (ultrasonic method). Using such a method, metal nanowires with desirablely adjusted thickness non-uniformity can be obtained.

[0032] Examples of metals constituting the above metal compound include silver, gold, copper, platinum, nickel, aluminum, and tin. Silver is preferred among these. Examples of the above metal compound include metal oxides, inorganic metal salts, and organometallic salts of the above metal. Examples of the above inorganic metal salt include nitrates, sulfates, oxalates, chlorides, hydroxides, sulfites, thiosulfates, persulfates, pernitrates, and hyponitrites. Examples of the above organometallic salt include metal acetate, metal propionate, metal butyrate, metal valerate, metal hexanoate, and other metal carboxylate salts and metal sulfonates.

[0033] Examples of the above-mentioned organic acids include carboxylic acids, acetic acid, propionic acid, butyric acid, valeric acid, and hexanoic acid. Among these, carboxylic acids are preferred.

[0034] The solvent may be an aqueous solvent or an organic solvent. An example of an aqueous solvent is water. An example of an organic solvent is alcohol (e.g., ethanol).

[0035] Any suitable method can be used to reduce the above organometallic salt. Examples include plasma reduction, photoreduction, laser irradiation reduction, and solid-gas reduction. In solid-gas reduction, the organometallic salt is reduced by contacting a fibrous organometallic salt with a gaseous reducing agent. In one embodiment, the transparent conductive layer can be formed by coating (applying and drying) a coating solution (precursor ink) containing a fibrous organometallic salt and a solvent onto a substrate, and then reducing the organometallic salt in the coating layer.

[0036] The above ultrasonic method for manufacturing metal nanowires is described, for example, in International Publication No. 2015 / 030045. The description in said publication is incorporated herein by reference.

[0037] The transparent conductive layer described above may contain a binder resin. For example, a transparent conductive layer containing a binder resin can be formed by using a composition for forming a transparent conductive layer that contains a binder resin. Any suitable resin can be used as the binder resin. Examples of such resins include acrylic resins; polyester resins such as polyethylene terephthalate; aromatic resins such as polystyrene, polyvinyltoluene, polyvinylxylene, polyimide, polyamide, and polyamideimide; polyurethane resins; epoxy resins; polyolefin resins; acrylonitrile-butadiene-styrene copolymer (ABS); cellulose; silicone resins; polyvinyl chloride; polyacetate; polynorbornene; synthetic rubber; and fluororesins. The binder resin may be used alone or in combination with other resins.

[0038] In one embodiment, a curable resin is used as the binder resin. Examples of curable resins include polyfunctional acrylic resins. The curable resin can be obtained from a monomer composition containing a polyfunctional monomer. Examples of polyfunctional monomers include tricyclodecanedimethanol diacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol tetra(meth)acrylate, dimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol(meth)acrylate, 1,9-nonanediol diacrylate, 1,10-decanediol(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dipropylene glycol diacrylate, isocyanuric acid tri(meth)acrylate, ethoxylated glycerin triacrylate, and ethoxylated pentaerythritol tetraacrylate. Polyfunctional monomers may be used individually or in combination.

[0039] The basis weight of the transparent conductive layer is preferably 0.001 g / m². 2~0.09g / m 2 Therefore, more preferably 0.005 g / m 2 ~0.05g / m 2 That is the case.

[0040] When the transparent conductive layer contains a binder resin, the content ratio of metal nanowires in the transparent conductive layer is preferably 0.1 to 50 parts by weight, and more preferably 0.1 to 30 parts by weight, per 100 parts by weight of the binder resin constituting the transparent conductive layer. Within this range, a transparent conductive film with excellent conductivity and transparency can be obtained.

[0041] D. Method for manufacturing transparent conductive film The transparent conductive film described above can be formed, for example, by coating the substrate with a composition for forming a transparent conductive layer.

[0042] In one embodiment, the composition for forming a transparent conductive layer comprises a binder resin and metal nanowires. The composition for forming a transparent conductive layer, comprising the binder resin, may also contain any suitable solvent.

[0043] In another embodiment, the composition for forming the transparent conductive layer is a precursor ink containing the fibrous organometallic salt and a solvent. In this embodiment, metal nanowires are obtained by a so-called ultrasonic method. Also in this embodiment, the transparent conductive layer is formed by reducing the fibrous organometallic salt after applying the composition for forming the transparent conductive layer (precursor ink). The method for forming the transparent conductive layer in this embodiment is described, for example, in International Publication No. 2015 / 030045. The description in said publication is incorporated herein by reference.

[0044] The composition for forming a transparent conductive layer may further contain any suitable additives depending on the purpose. Examples of such additives include corrosion inhibitors that prevent corrosion of metal nanowires and surfactants that prevent aggregation of metal nanowires. The composition for forming a transparent conductive layer may also contain additives such as plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, ultraviolet absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, thickeners, inorganic particles, surfactants, and dispersants.

[0045] Any suitable method can be used to apply the above-mentioned transparent conductive layer forming composition. Examples of application methods include spray coating, bar coating, roll coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, intaglio printing, and gravure printing. Any suitable drying method (e.g., natural drying, forced-air drying, and heat drying) can be used to dry the coated layer. For example, in the case of heat drying, the drying temperature is typically 80°C to 150°C, and the drying time is typically 1 to 20 minutes. [Examples]

[0046] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The evaluation method in the examples is as follows. The thickness was measured using a scanning electron microscope "S-4800" manufactured by Hitachi High-Technologies Corporation after forming a cross-section by cutting with an ultramicrotome following embedding treatment with epoxy resin.

[0047] (1) Absorbance Using a UV-Vis-Near-Infrared spectrophotometer (Shimadzu Corporation, product name "UV-3150"), the absorbance at a wavelength of 550 nm (Abs(550nm)) and at a wavelength of 360 nm (Abs(360nm)) was measured, and (Abs(360nm) / Abs(550nm)) was calculated. (2) Surface resistance The surface resistance of a transparent conductive film was measured using the eddy current method with a non-contact surface resistance meter, product name "EC-80," manufactured by Napson Corporation. The measurement temperature was 23°C. (3) Hayes Measurements were taken using the "HR-100" product manufactured by Murakami Color Research Institute Co., Ltd. The measurement temperature was set to 23°C. The average value of three repeated measurements was used as the measured value. (4) Total light transmittance Measurements were taken using the "HR-100" product manufactured by Murakami Color Research Institute Co., Ltd. The measurement temperature was set to 23°C. (5) Thickness of metal nanowires Using a FE-SEM (Hitachi High-Tech Corporation, product name "SU8200"), the surface of a transparent conductive film was observed, and the thickness of metal nanowires was measured. Within each of five randomly selected areas (3.0 μm × 2.0 μm), the thickness of five randomly selected metal nanowires was measured. From the measurements of the five areas × five nanowires, the maximum, minimum, mean, and standard deviation of the metal nanowire thickness were determined.

[0048] [Example 1] 100 mL of ethanol (99.5% purity, manufactured by Wako Pure Chemical Industries, Ltd.) in an Erlenmeyer flask was degassed for 10 minutes at an RF frequency of 44.34 kHz and an output of 100 W using an ultrasonic transducer (manufactured by Sharp Corporation, product name "UI-304R") connected to a function generator (manufactured by NF Circuit Design Block Co., Ltd., product name "WF1973"), and 167 μL of acetic acid (manufactured by Wako Pure Chemical Industries, Ltd.). Then, the mixture was subjected to ultrasonic waves at an RF frequency of 96.87 kHz and an output of 100 W for 2 hours in water at 40°C to obtain a precursor ink. The obtained precursor ink was coated onto a substrate (cycloolefin polymer (COP) film) using a wire bar #40, dried in an 80°C oven (ESPEC Corporation, product name "SPH-201") for 1 minute, and then the petri dish containing the precursor film and weighing paper was placed on a hot plate (AS ONE Corporation, product name "HHP-411") heated to 170°C. One drop of hydrazine monohydrate (Wako Pure Chemical Industries, Ltd.) was added to the weighing paper, the lid was closed, and the weighing paper was exposed to hydrazine vapor for 1 minute to reduce it and produce a transparent conductive film (substrate / transparent conductive layer (thickness: 1.0 μm)). The obtained transparent conductive film was subjected to the above evaluation. The results are shown in Table 1.

[0049] [Example 2] A transparent conductive film was obtained in the same manner as in Example 1, except that the wire bar #40 used when coating the precursor ink was changed to wire bar #38, and a transparent conductive layer with a thickness of 0.95 μm was formed. The obtained transparent conductive film was subjected to the above evaluation. The results are shown in Table 1.

[0050] [Example 3] A transparent conductive film was obtained in the same manner as in Example 1, except that the wire bar #40 used when coating the precursor ink was changed to wire bar #34, and a transparent conductive layer with a thickness of 0.85 μm was formed. The obtained transparent conductive film was subjected to the above evaluation. The results are shown in Table 1.

[0051] [Example 4] A transparent conductive film was obtained in the same manner as in Example 1, except that the wire bar #40 used when coating the precursor ink was changed to wire bar #32, and a transparent conductive layer with a thickness of 0.80 μm was formed. The obtained transparent conductive film was subjected to the above evaluation. The results are shown in Table 1.

[0052] [Comparative Example 1] (Synthesis of silver nanowires and preparation of silver nanowire dispersions) In a reaction vessel equipped with a stirring device, at 160°C, 5 ml of anhydrous ethylene glycol and a solution of PtCl2 containing anhydrous ethylene glycol (concentration: 1.5 × 10⁻⁶) are mixed. -40.5 ml of (mol / L) was added. After 4 minutes, 2.5 ml of anhydrous ethylene glycol solution of AgNO3 (concentration: 0.12 mol / L) and 5 ml of anhydrous ethylene glycol solution of polyvinylpyrrolidone (MW: 55000) (concentration: 0.36 mol / L) were simultaneously added dropwise over 6 minutes to the resulting solution. After this addition, the mixture was heated to 160°C and the reaction was carried out for more than 1 hour until the AgNO3 was completely reduced to produce silver nanowires. Next, acetone was added to the reaction mixture containing the silver nanowires obtained as described above until the volume of the reaction mixture was increased fivefold. The reaction mixture was then centrifuged (2000 rpm, 20 minutes) to obtain silver nanowires. Silver nanowire dispersion I was prepared by dispersing the silver nanowire (concentration: 0.2 wt%) and pentaethylene glycol dodecyl ether (concentration: 0.1 wt%) in pure water. (Manufacturing of transparent conductive film) A cycloolefin resin film was used as the substrate. A silver nanowire dispersion I was applied to this substrate and dried. Next, as the material for forming the overcoat layer, resin composition A was prepared by blending 80 parts by weight of "Unidic ELS-888" (manufactured by DIC Corporation) and 20 parts by weight of "Unidic RS28-605" (manufactured by DIC Corporation). This resin composition A was applied to the conductive layer and exposed to ultraviolet light at an exposure dose of 230 mJ / cm². 2 Irradiation was performed to form a polymer matrix, and a transparent conductive film was obtained. The obtained transparent conductive film was subjected to the above evaluation. The results are shown in Table 1.

[0053] [Table 1]

[0054] The transparent conductive films of Examples 1-4 shown in Table 1 are advantageous in that they have a small (Abs(360nm) / Abs(550nm)) ratio and minimal coloration. Such transparent conductive films can be obtained by adjusting the uniformity of the thickness of the metal nanowires. [Explanation of symbols]

[0055] 10 Base material 20 Transparent conductive layer 100 Transparent conductive film

Claims

1. A transparent conductive film comprising a substrate and a transparent conductive layer disposed on at least one side of the substrate, The transparent conductive layer contains metal nanowires, The total light transmittance of the transparent conductive film is 60% or more. The surface resistance of the transparent conductive film is 10 Ω / □ to 200 Ω / □. The ratio of the absorbance at a wavelength of 360 nm to the absorbance at a wavelength of 550 nm of the transparent conductive film (Abs(360 nm) / Abs(550 nm)) is 1.07 to 2.

0. Transparent conductive film.

2. The transparent conductive film according to claim 1, wherein the standard deviation of the thickness of the metal nanowires is 3 nm to 25 nm.

3. The transparent conductive film according to claim 1, wherein the coefficient of variation of the thickness of the metal nanowire is 0.13 to 0.4.

Citation Information

Patent Citations

  • Steamer

    JP1986099034A

  • Transparent conductors based on nanowires

    JP2009505358A

  • Transparent conductive film, its manufacturing method and touch panel using transparent conductive film

    JP2011096537A

  • Transparency film with light hue controlled using nanoscale colorants

    JP2017539047A

  • Transparent conductive substrate

    JP2022040154A